2008
DOI: 10.1111/j.1468-2982.2008.01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Headache and Temporomandibular Disorders Related? A Blinded Study

Abstract: To investigate overlaps between headache and temporomandibular disorders (TMD) in a clinical headache population and to describe the prevalence of TMD in headache patients, 99 patients referred to a specialized headache centre were diagnosed according to Research Diagnostic Criteria for TMD (RDC/TMD) and classified in headache groups according to the International Classification of Headache Disorders, second edition for headache diagnoses in a blinded design. The prevalence of TMD in the headache population wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
93
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 62 publications
10
93
2
5
Order By: Relevance
“…Menstrual migraine is well known to be more severe and refractory to treatment than non-menstrual migraine 10,24 , and a limitation of our study was not to characterize this migraine subgroup, since this would require longitudinal follow-up and use of dairies. We found strong association between migraine and TMD pain, as previously described 10,[12][13][14][15][16][17][18][19][20] . Gonçalves et al, in a population-based study, found that TMD symptoms are more likely to occur among those who present any headache type.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Menstrual migraine is well known to be more severe and refractory to treatment than non-menstrual migraine 10,24 , and a limitation of our study was not to characterize this migraine subgroup, since this would require longitudinal follow-up and use of dairies. We found strong association between migraine and TMD pain, as previously described 10,[12][13][14][15][16][17][18][19][20] . Gonçalves et al, in a population-based study, found that TMD symptoms are more likely to occur among those who present any headache type.…”
Section: Discussionsupporting
confidence: 87%
“…Gonçalves et al, in a population-based study, found that TMD symptoms are more likely to occur among those who present any headache type. When three or more TMD symptoms were present, headache occurred in 72.8% versus 37.9% of those who did not present any TMD symptoms 13 , as confirmed by others 15 . Furthermore, when assessing a clinic-based sample, they found that the comorbidity of TMD with migraine, CDH, and TTH, happened only for the muscular form, and not for the articular type 18 .…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…C'est aussi une région où il importe de tirer profit de l'expertise des intervenants des domaines dentaire et médical lors de l'investigation des états douloureux qui s'accompagnent d'un cortège de symptômes et de manifestations allant bien au-delà des limites topographiques des structures d'où peut provenir la douleur. Les maux de tête, les cervicalgies, les otalgies et acouphènes dont se plaignent souvent ceux souffrant de désordres temporomandibulaires en sont un bel exemple [1,7]. Et que dire des douleurs orofaciales hétérotopiques, comme celles d'origine cardiaque, susceptibles de mettre la vie du patient en danger [5] ?…”
unclassified